Concept of Thinking about Strategies to Increase Chicken Production - Yuliyananda, Devi; Arisandi, Bayu (Jurnal Agrosci, 2024)
Efforts to increase the production of free-range chickens can be carried out through several strategies, including Early Separation of Chicks and Mothers, separation of chicks from their mothers from an early age to reduce the period when chickens stop laying eggs because they take care of their offspring for approximately 105 days. Early separation can extend the egg-laying period to more than 15 days. Use of Intensive Maintenance Patterns: Replace extensive maintenance patterns with more efficient intensive patterns. The intensive pattern involves the use of closed cages and more controlled feeding, which can improve the quality and quantity of nutrients in the feed as well as the number of chickens raised, the crossing of Kampung Roosters with Laying Breed Females, The crossing between Kampung Roosters and laying breed females can increase the production of kampung chickens. Estimating the physical appearance of a chicken's body, such as feather color, shank length, chest width, body length, and beard shape, can be used to estimate the production of free-range chickens. Genetic Selection is conducting genetic selection to select livestock that have superior genetic quality. This is done by selecting broodstock based on egg production, number, and weight. This selection process requires individual production records and daily mixing of mothers and males to improve egg fertility and hatchability. Use of Modern Technology, using technologies such as brooding (giving a warming lamp) to create conditions similar to those produced by hens. This helps to nurture the chicks when they are newly hatched. By implementing this strategy, the production of free-range chickens can be increased to meet high market demand.